Intergenerational Education Mobility in Africa : Has Progress Been Inclusive? - Azomahou, Theophile T.; Yitbarek, Eleni A. (World Bank, Washington, DC, 2016)
This paper employs nationally representative household survey data on parents of adult individuals to analyze the intergenerational transmission of education in nine Sub-Saharan African countries. The paper provides the levels, trends, and patterns of intergenerational persistence of educational attainment over 50 years, with a special focus on gender differences. The study finds a declining cohort trend in the intergenerational educational persistence in all the countries, particularly after the 1960s. The increase in educational mobility coincides with drastic changes in educational systems and a huge investment in human capital accumulation in the region following independence. Nevertheless, the education of parents' remains a strong determinant of educational outcomes among the children in all the countries. Ghana, Guinea, Nigeria, and Uganda experienced the highest intergenerational mobility, and the Comoros and Madagascar the lowest. In all the sample countries, more mobility is observed in the lower tail of the distribution of education. Intergenerational educational persistence is strong from mothers to children, and the effect is more pronounced among daughters than sons. The results highlight the need for targeted redistributive policies that improve intergenerational mobility in the region.